Environmental Effects of Urban and Peri-Urban Agriculture in Kisii Town, Kenya - Okwoyo, Amos Mogire (JOOUST, 2022)
The purpose of the study was to determine the effects of urban and peri-urban agriculture on the environment in Kisii, Kenya. This is due to fact that the concept of Urban and Peri-Urban Agriculture (UPA) is beginning to gain popularity around the world. Though UPA has been practiced for many years throughout the world, it has been viewed with concern and with some as undesirable. Promoting safe food production and urban food distribution has faced many challenges, especially from opponents of urban agriculture worried about potential health risks to produce and distribute food in urban areas. Many of the previous studies have largely focused on its role in food security and economic benefits but no major studies have been done to document its environmental implication scales. Therefore, the main goal of the study was to investigate the environmental effects of UPA practices in Kenya, narrowed down to Kisii town. The specific objectives were to establish the typology of UPA in Kisii town, determine the environmental effects of UPA in Kisii town and make suggestions for effective implementation of UPA while conserving the urban environment. The study consisted of 360 urban household farmers who were selected through cluster sampling and purposive sampling techniques. Purposive sampling was employed for key informants who included County Director of Agriculture, County Director of Physical Planning, County Director Public Health and County Director of National Environment Management Authority. Out of the 360 questionnaires, only 296 were returned accounting for 82.2 response rate. The quantitative research design was adopted since the collected data needed to be coded into numerical format for analysis. The data was collected using questionnaires, interviews, observations checklists and photographs. The data was analyzed using simple descriptive statistics such as frequencies and percentages, as well as multiple linear regression. The results obtained indicated that famers in the study area practice both peri- urban and intra-urban agriculture, with 79.05% of the farms being located in the peri-urban areas and only 20.95% of them were intra-urban farms. Regarding UPA typologies, it was observed that crop production was the most common type of UPA within Kisii town while livestock rearing was the least common. Based on regression analysis, crop production had the greatest impact with regression coefficient of 0.511 while livestock had the least impact with a regression coefficient of 0.020. Agroforestry was second in terms of environmental impact while mixed farming was third in terms Of its environmental impact with a regression coefficient of 0.14. The government officials interviewed had reservations against UPA. They were of the view that urban famers dot not practice UPA in safe environmental conditions with others using dirty and contaminated water for irrigation while livestock are left loitering in estates and others feed on garbage which could be contaminated. They recommended UPA to be promoted if it’s done in safe conditions like the one done by Kisii Agricultural Training Centre. The study concludes that UPA can support the sustainability of urban centers through productive urban green infrastructure including storm water retention, urban heat reduction and soil erosion control while still giving much-needed food to a significant number of people. The study recommends the legalizing of UPA to enable farmers get support from non-governmental and government agencies so as to encourage environmentally friendly farming practices. The study also recommends promotion of sustainable livestock production through workshops, training, and farmers’ educational tours as part of extension services; providing infrastructural services and increasing accessibility to markets to enhance UPA sustainability.